Metode Pembelajaran Iqro’ Di TPQ Al-Ikhlas Di Desa Ngaresrejo - Mas Aqibus Sani Al-Farisi; Luky Dwi Hartanto; Masfufah Masfufah; Eli Masnawati; Amir Bandar Abdul Majid; Wakid Evendi; Muhammad Zakki (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
In Ngaresrejo Village, TPQ Al-Ikhlas managed to overcome the challenge of a limited number of teachers by using the Iqro' method which is not only interesting but also adapted to the characteristics of students. By utilizing the ABCD (Asset Based Communities Development) approach model in community development, TPQ Al-Ikhlas is able to maximize potential by focusing on its assets, namely the significant number of students. The TPQ learning program has the main objective of improving religious understanding, and the results are seen through the students' increased insight into Arabic writing, recitation of Hijaiyah letters, as well as memorization of daily prayers, short letters, and prayer recitations. By successfully implementing this method, TPQ has not only overcome the limited number of teachers, but also made a positive contribution to improving the religious knowledge and practical skills of its students.